2013
DOI: 10.1089/humc.2012.244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulators and Promoters for Expression of the Wiskott–Aldrich Syndrome Protein Using Lentiviral Vectors

Abstract: Gene therapy for the treatment of Wiskott-Aldrich syndrome (WAS) presents an alternative to the current use of allogeneic bone marrow transplantation. We describe the development of a self-inactivating lentiviral vector containing chromatin insulators for treatment of WAS and compare a gammaretroviral (MND), human cellular (EF1α), and the human WASp gene promoter for expression patterns in vivo during murine hematopoiesis using the green fluorescent protein (GFP) marker. Compared with the EF1α and the WASp pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…49 We have also found that the g-retroviral promoter is much stronger than either the EF1a or the WAS 1.6-kb promoter in various model systems. 50 Several other studies suggested that a 1.6-kb promoter fragment from the WASp gene achieves adequate levels for correction in the preclinical model as well as normal levels of expression in human CD341 cells.…”
Section: Wasmentioning
confidence: 99%
“…49 We have also found that the g-retroviral promoter is much stronger than either the EF1a or the WAS 1.6-kb promoter in various model systems. 50 Several other studies suggested that a 1.6-kb promoter fragment from the WASp gene achieves adequate levels for correction in the preclinical model as well as normal levels of expression in human CD341 cells.…”
Section: Wasmentioning
confidence: 99%
“…19,20 The MND(U3) region of a modified gammaretroviral LTR is a strong promoter/enhancer, and has been previously successfully used internally in an LV vector in a clinical trial of gene therapy for adrenoleukodystrophy, without evidence of genotoxicity after 10 years of follow-up; it has also been shown to adequately correct the WAS phenotype in preclinical studies. [33][34][35] To avoid high expression of a pore-forming protein in HSPCs, we restricted expression in HSPCs by using miR126 target elements. 25,26 Transgene expression in HSPCs in globoid leukodystrophy was found to be toxic to HSPCs, which was overcome by placing miR126 target sites in the vector.…”
Section: Discussionmentioning
confidence: 99%
“…In previous mouse gene therapy experiments, we found that the WS1.6 promoter did not effectively rescue WASp expression in all lineages including B cells and resulted in the acquisition of features of humoral autoimmunity 20 . In contrast, an SIN-LV using a synthetic promoter derived from a γ-retrovirus called MND (MPSV LTR, NCR deleted, dl587 PBS) 26 as an internal promoter rescued WASp expression in all affected lineages and reduced the risk of autoimmunity 20, 27, 28…”
Section: Introductionmentioning
confidence: 93%
“…Although strongly trans -activating promoters are associated with an enhanced risk of insertional transactivation, this risk can be diminished by including a chromatin insulator 28, 30, 31. Chromatin insulators act as boundary elements preventing interactions between adjacent chromatin domains 32, 33, 34.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation